Association between socio-economic factors and HIV self-testing knowledge amongst South African women - Michael Ekholuenetale; Chimezie I. Nzoputam; Osaretin C. Okonji (AOSIS, 2022)
Background: Self-testing for HIV is an effective and alternative method of increasing HIV testing rates and a strategy for reaching populations that are underserved by HIV testing services. Nonetheless, many resource-constrained settings are yet to adopt HIV self-testing (HIVST) into their national HIV programmes. Objectives: This study aimed to examine the association between socio-economic factors and HIVST knowledge amongst South African women. Method: We used nationally representative data from the 2016 South African Demographic and Health Survey. A sample of 8182 women of reproductive age was analysed. The outcome variable was HIVST knowledge. This was measured dichotomously; know versus do not know about HIVST. The multivariable logistic model was used to examine the measures of association, with the level of significance set at P  0.05. Results: The prevalence rate of HIVST knowledge was found to be approximately 24.5% (95% confidence interval [CI]: 22.9-26.1) amongst South African women. Women with tertiary education were 3.93 times more likely to have HIVST knowledge, when compared with those with no formal education (odds ratio [OR]: 3.93; 95% CI: 1.37-11.26). Rural residents had a 33% reduction in HIVST knowledge when compared with those residing in urban areas (OR: 0.67; 95% CI: 0.51-0.89). The odds of interaction between the richer and richest women who have good knowledge of HIV infection were 1.88 and 2.24 times more likely to have HIVST knowledge, respectively, when compared with those from the poorest wealth household who have good knowledge of HIV infection. Conclusion: Based on the low level of HIVST knowledge, the findings emphasise the importance of developing effective HIVST educational campaigns. Moreover, programmes should be designed to address the unique needs of the socio-economically disadvantaged women.